1997
DOI: 10.1006/anbo.1997.0479
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Progress towards Flowering and Podding in Bambara Groundnut (Vigna subterranea) as a Function of Temperature and Photoperiod

Abstract: The influence of temperature and photoperiod on phenological development of three bambara groundnut (Vigna subterranea) selections from Botswana, Zimbabwe and Mali was investigated in a semi-controlled environment experiment with factorial combinations of three constant temperatures (20n9, 23n4 and 26n2 mC) and four constant photoperiods (10n0, 12n5, 13n5 and 16n0 h d −" ). In all three selections, the onset of flowering was influenced by temperature but not by photoperiod, while the onset of pod-growth (' pod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 23 publications
3
24
1
Order By: Relevance
“…Moreover, a highly controlled environment is needed for such phenotyping in most ecologies (especially in the tropical regions where natural day length variation is limited). However, studies focusing on photothermal response mechanisms in Bambara groundnut have been reported (Linnemann 1991;Linnemann et al 1995;Brink 1997Brink , 1999Brink et al 2000;Jørgensen et al 2009;Kendabie et al 2014). The opportunity to use molecular markers linked to QTLs associated with photo-thermal response could be useful in future germplasm characterization.…”
Section: Overview Of Qualitative and Quantitative Phenotypic Diversitmentioning
confidence: 99%
“…Moreover, a highly controlled environment is needed for such phenotyping in most ecologies (especially in the tropical regions where natural day length variation is limited). However, studies focusing on photothermal response mechanisms in Bambara groundnut have been reported (Linnemann 1991;Linnemann et al 1995;Brink 1997Brink , 1999Brink et al 2000;Jørgensen et al 2009;Kendabie et al 2014). The opportunity to use molecular markers linked to QTLs associated with photo-thermal response could be useful in future germplasm characterization.…”
Section: Overview Of Qualitative and Quantitative Phenotypic Diversitmentioning
confidence: 99%
“…In Vigrca subterranea, Linnemann [106] observed an effect of the photoperiod on the flowering time and Linnemann and Craufurd [ 107] revealed differences between genotypes, as only one among the three genotypes analyzed was responsive to photoperiod. Brink [22] found that the flowering time only depended on the temperature but that the time to podding was affected by the photoperiod. This post-flowering effect of the photoperiod was also observed on soybean [62] and groundnut [52].…”
Section: Genetic Variation In the Responsementioning
confidence: 99%
“…In most bambara groundnut genotypes investi- ) against days after sowing for bambara groundnut sown on 21 December, 18 January and 18 February, 2007-08 cropping season. Vertical bars indicate SE of means gated, including some of the landraces used in this study, the onset of flowering is photoperiod-insensitive but the onset of podding is retarded by long photoperiods (Linnemann 1994;Brink 1997;Sesay et al, 2008). In a preliminary field experiment in Botswana, Harris and Azam-Ali (1993) reported that pod development in bambara groundnut was fastest at daylengths shorter than about 12 h and slowed as daylength increased.…”
Section: Resultsmentioning
confidence: 89%
“…However, the consistent declining trends in crop performance with delay in sowing in this study may be associated not only with the seasonal decline in temperatures, but also with seasonal changes in photoperiod. Studies in a controlled environment (Linnemann & Craufurd, 1994;Brink, 1997) and field environment (Harris & Azam-Ali, 1993;Sesay et al, 2008) have strongly indicated the dominant role of photoperiod in the control of reproductive development in bambara groundnut. In most bambara groundnut genotypes investi- ) against days after sowing for bambara groundnut sown on 21 December, 18 January and 18 February, 2007-08 cropping season.…”
Section: Resultsmentioning
confidence: 99%